NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD): DISEASE MECHANISMS AND CONTEMPORARY THERAPEUTIC APPROACHES - A LITERATURE REVIEW - Konrad Strużek,; Agnieszka Kwiatkowska,; Ewelina Mączka,; Wiktor Tracz,; Patrycja Świercz,; Kinga Teper,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka,; Aleksandra Ewa Basak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide, representing a significant public health challenge. Over the past decades, it has been recognized as a multisystem disease closely associated with type 2 diabetes mellitus (T2DM), cardiovascular diseases (CVD), and chronic kidney disease (CKD).Objective: The aim of this review is to discuss contemporary pathogenetic mechanisms underlying NAFLD as well as current and experimental therapeutic strategies, encompassing non-pharmacological, pharmacological, and microbiota-targeted interventions.Methods: An analysis and synthesis of data from preclinical studies, clinical trials (phases II and III), meta-analyses, and recommendations of scientific societies published over the past two decades was conducted. The review includes works indexed in PubMed, Scopus, and Web of Science databases, with a focus on NAFLD and NASH therapies.Conclusions: NAFLD is a complex disease with a heterogeneous pathogenesis, in which lipotoxicity, cellular stress, gut dysbiosis, and insulin resistance play key roles. The most well-documented therapeutic approach remains lifestyle modification (Mediterranean diet, physical activity). Promising effects have been demonstrated by certain agents used in the treatment of type 2 diabetes (e.g., GLP-1 receptor agonists, SGLT2 inhibitors, pioglitazone) as well as novel molecules such as FXR agonists, THR-β agonists, and FGF19/FGF21 analogues. Further clinical studies are necessary to validate the efficacy and safety of these therapies.